PENGELOLAAN ANGGARAN BIAYA OPERASIONAL UNTUK MENINGKATKAN EFISIENSI PENGGUNAAN ANGGARAN PADA PT. SENTANA ADIDAYA PRATAMA CABANG PALEMBANG - Haikal, Haikal (Jurnal Manajemen, 2019)
This study aims to determine the management of the cost budget and the factors that influence the increased efficiency of budget use at PT. Sentana Superpower Pratama Palembang Branch. This research is descriptive. The results of this study indicate that PT. Sentana Superpower Pratama Palembang Branch reports the results of the implementation of operational costs have been carried out as it should. Where in the report presents comparisons and differences between the budget and its realization. And from this budget execution report, company management can immediately conduct an evaluation so that the difference does not occur again in the next period.